Paciente femenino de 55 años con neumonía asociada a la ventilación mecánica. - Nivela Vera, María Gabriela (2021)
This clinical case involves a 50-year-old patient who was diagnosed with HIV and ventilator-associated pneumonia, which were complications after admission to the intensive care unit. Pneumonia associated with mechanical ventilation is one of the main causes of death in mechanically ventilated patients, either by tracheostomy or tracheal intubation, this complication occurs because the secretions accumulated in the airways cannot be eliminated by themselves. Through this research, we will understand what risk factors cause and lead to contracting pneumonia associated with mechanical ventilation, which in turn will know what measures must be taken to avoid such complications.